A Rare Concomitant Oncocytic Adrenocortical Neoplasm and Hepatocellular Carcinoma over a Four-year Duration: A Case Report and Review of Literature. (20th October 2019) - Saleh, Daniyah; Gomaa, Wafaey; Al-Maghrabi, Jaudah
Abstract : Oncocytic adrenocortical neoplasms (OANs) are very rare. Although most cases have benign behavior, the risk of recurrence/metastasis is variable. Based on Lin-Weiss-Bisceglia (LWB) system criteria, OANs can be classified as benign, borderline, or malignant. A concomitant development of OANs with second primary neoplasm is extremely uncommon, and is limited to very few case reports. None of these reported cases was found to be associated with hepatocellular carcinoma (HCC). In this case report, we present a 64-year-old female patient who had a progressively increasing left supra-renal mass over a three-year interval. During her regular imaging-based follow up after successful left adrenalectomy, a new suspicious solitary, hypodense liver mass was detected and removed. All necessary work-up was done and strongly support the diagnosis of two distinct primary tumors including borderline malignant potential OAN and subsequent HCC. A significant clinical and morphological characteristic of OANs make its identification valuable.